2020
DOI: 10.3390/sports8120151
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Barbell Hip Thrust on Post-Activation Performance Enhancement of Change of Direction Speed in College-Aged Men and Women

Abstract: This study investigated whether the barbell hip thrust (BHT) enhanced change-of-direction (COD) speed measured by the 505 COD speed test. Forty recreationally trained individuals completed three sessions. Session 1 included one-repetition maximum (1RM) BHT testing to measure absolute and relative strength. Sessions 2 and 3 involved two counter-balanced conditioning activities (CAs): 3 sets × 5 repetitions of the BHT at 85% 1RM and a control condition (CC; 6 min rest). The 505 COD speed test was performed 5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The underlying mechanisms for PAPE have been primarily attributed to the following physiological effects: positive changes of muscle temperature, fiber water content, and muscle activation [1,[5][6][7]. Although there is no evidence regarding the exact mechanisms, the acute benefits of PAPE have been observed in several explosive movements such as jumping [8,9], throwing [10][11][12], sprinting [13][14][15], and changing of the direction [16]. Therefore, the ability to harness PAPE effects to maximize athletic performance has received intensive attention [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms for PAPE have been primarily attributed to the following physiological effects: positive changes of muscle temperature, fiber water content, and muscle activation [1,[5][6][7]. Although there is no evidence regarding the exact mechanisms, the acute benefits of PAPE have been observed in several explosive movements such as jumping [8,9], throwing [10][11][12], sprinting [13][14][15], and changing of the direction [16]. Therefore, the ability to harness PAPE effects to maximize athletic performance has received intensive attention [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the decreased sensitivity is a result of the decreased relationship of calcium/troponin or reduced strength production of cross-bridge formation during contraction (Rassier & Macintosh 2000). Orjalo et al reported that barbell hip thrust PAP activity (85 % of 1RM, 3 sets x 5 repetitions) positively influenced the change of direction performance of both males (23.95 ± 3.24 years) and females (22.60 ± 2.21 years) in the 4 th (p < 0.001), 8 th (p < 0.004), 12 th (p < 0.028), and 16 th minutes (p < 0.001) (Orjalo et al 2020). In the mentioned research, the 5-0-5 test was used for the change of direction performance.…”
Section: Discussionmentioning
confidence: 98%
“…Bevan et al showed that the jump squat conditioning activity caused better sprint performance in the 8 th minutes than 4-12-16 th minutes (Bevan et al 2010). In another study Orjalo et al (2020) showed that the barbell hip thrust conditioning activity led to an improvement in the change of direction performance in 4-8-12, and 16 th minutes. In addition to the importance of rest intervals to create the PAP effect (Bevan et al 2009(Bevan et al , 2010Kilduff et al 2008;Zois et al 2011), it is well-known that the PAP mostly is a personalized response (Lockie et al 2018).…”
Section: Introductionmentioning
confidence: 94%
“…The study's sample size was pre-estimated using G*Power 3.1.9.7 software (Dusseldorf, Germany), selecting the “MANOVA: Repeated measures, within-between interaction” option. Effect Size (V), α err Prob, and Power (1-β err Prob) were set at 0.8, 0.05, and 0.95, respectively [ 19 ]. The estimation results indicated a minimum sample size requirement of 18 individuals.…”
Section: Methodsmentioning
confidence: 99%